The use of full-setting non-invasive ventilation in the home care of people with amyotrophic lateral sclerosis-motor neuron disease with end-stage respiratory muscle failure: a case series - de Vito, Eduardo (2012)
INTRODUCTION: Little has been written about the use of non-invasive ventilation in the home care of amyotrophic lateral sclerosis-motor neuron disease patients with end-stage respiratory muscle failure. Nocturnal use of non-invasive ventilation has been reported to improve daytime blood gases but continuous non-invasive ventilation dependence has not been studied in this regard. There continues to be great variation by country, economics, physician interest and experience, local concepts of palliation, hospice requirements, and resources available for home care. We report a case series of home-based amyotrophic lateral sclerosis-motor neuron disease patients who refused tracheostomy and advanced non-invasive ventilation to full-setting, while maintaining normal alveolar ventilation and oxygenation in the course of the disease. Since this topic has been presented in only one center in the United States and nowhere else, it is appropriate to demonstrate that this can be done in other countries as well. CASE PRESENTATION: We present here the cases of three Caucasian patients (a 51-year-old Caucasian man, a 45-year-old Caucasian woman and a 57-year-old Caucasian woman) with amyotrophic lateral sclerosis who developed continuous non-invasive ventilation dependence for 15 to 27 months without major complications and were able to maintain normal CO2 and pulse oxyhemoglobin saturation despite a non-measurable vital capacity. All patients were wheelchair-dependent and receiving riluzole 50 mg twice a day. Patient one developed mild-to-moderate bulbar-innervated muscle weakness. He refused tracheostomy but accepted percutaneous gastrostomy. Patient two had two lung infections, acute bronchitis and pneumonia, which were treated with antibiotics and cough assistance at home. Patient three had three chest infections (bronchitis and pneumonias) and asthmatic episodes treated with antibiotics, bronchodilators and cough assistance at home. All patients had normal speech while receiving positive pressure; they died suddenly and with normal oxygen saturation. CONCLUSIONS: Although warned that prognosis was poor as vital capacity diminished, our patients survived without invasive airway tubes and despite non-measurable vital capacity. No patient opted for tracheos tomy. Our patients demonstrate the feasibility of resorting to full-setting non-invasive management to prolong survival, optimizing wellness and management at home, and the chance to die peacefully.